Adherence of the nursing team to patient safety actions in neonatal units - Mendes,Léia Arcanjo (2021)
ABSTRACT Objectives: to describe the nursing team’s adherence to patient safety actions in neonatal units using a validated instrument. Methods: a cross-sectional study, carried out through direct observation of the nursing team and descriptive analysis of 182 records of the “Checklist for patient safety in nursing care during hospitalization in Neonatal Intensive Care Units” in a hospital in the municipality of Belo Horizonte. Results: there was evidence of adherence greater than 90.0% in the units concerning the use of the identification wristband and guidance of the companions. It was identified 79.0% of absence on the checking of wristband identification and 59.0% of the absence of an evaluation of the crib wheels’ locks. Three of the 21 items included in the checklist did not show non-conformities. Conclusions: partial adherence to patient safety actions was observed, especially regarding the target of patient identification and prevention of falls, which exposes newborns to preventable adverse events.